A Health and Social Legacy for East London: Narratives of 'Problem' and 'Solution' around London 2012. (May 2013) - Thompson, Claire; Lewis, Daniel; Greenhalgh, Trisha; Taylor, Stephanie; Cummins, Steven
Policies and programmes that tackle neighbourhood deprivation have long been a feature of urban policy in the UK and elsewhere. Large-scale urban regeneration and neighbourhood renewal programmes have been deployed as the primary vehicle to improve the health and life chances of residents of deprived neighbourhoods. Often these areas have a long history of efforts at regeneration and redevelopment and, over time, have become labelled as 'problem areas' in need of constant intervention. The bid for the London 2012 Olympic and Paralympic Games was successful partly due to its promise to deliver a lasting health and social legacy by using the Games as a driver of regeneration in East London. Despite limited evidence for the effectiveness of such an approach, regeneration schemes tied to sporting events have emerged as popular strategies through which cities strive to enhance their urban fabric. Running through the core of the London 2012 bid was a discourse of East London as a 'problem' in need of a regeneration 'solution' that the Olympics uniquely could deliver. As a result, a wider narrative of East London was generated: as unhealthy; mired in poverty; desperate for jobs; with an inadequate and outdated built environment. The Olympic legacy was thus positioned as a unique once-in-a-lifetime solution 'accelerating' regeneration in East London, and delivering substantive change that either might not have happened, or would otherwise have taken decades. Through documentary analysis of published Government policy documents for the period 2002-2011, we demonstrate how the 'problem' of East London was used as political justification for London 2012. We argue that the Olympic legacy was deliberately positioned in neoliberal terms in order to justify substantial economic investment by the UK government and suit the needs of the International Olympic Committee. Finally, whilst acknowledging that regeneration may indeed result, we also speculate on the potential legacy and possible challenges for the people in East London left by this neoliberal and entrepreneurial strategy.